Persistence of quarterly earnings: an empirical investigation in Brazil - Renê Coppe Pimentel; Andson Braga de Aguiar (BBR: Brazilian Business Review)
The aim of this paper is to estimate and analyze quarterly earnings persistence. In addition, we explore if earnings persistence varies across firms based on size and corporate governance standards. We first estimate the parameter revision of earnings and then we test the hypotheses that the parameter of earnings persistence is different for firms with different sizes (H1) and corporate governance standards (H2). We collect data from Brazilian listed firms with quarterly earnings per share available at Economatica database from last quarter of 1995 to first quarter 2011. Our results indicate that for most of the firms the earnings persistence is not significantly different from zero. The main implication of this result is that most of quarterly earnings innovation is transitory. In addition, the results support our first hypothesis indicating that larger firms present higher parameter of earnings persistence. The results also indicate that the parameter of earnings persistence is different for firms with different corporate governance standards, partially supporting our second hypothesis.